WRITING ANXIETY EXPERIENCED BY JUNIOR HIGH SCHOOL STUDENTS - Rizal Arisman (Institut Agama Islam Negeri Parepare, 2023)
This research is aiming at knowing the students’ writing anxiety level, including cognitive, somatic, and avoidance behavior anxiety. It applies a quantitative approach a descriptive method. The sample is 55 eighth-grade students at SMP Negeri 4 Baubau selecting using a cluster random sampling technique. A SLWAI is utilized as the instrument of this research. The research finds that the average score of cognitive anxiety is 3.11 which is in moderate level of anxiety, the mean score of somatic anxiety is 3.14 which is in moderate category, and the mean score of avoidance behavior is 3.04 which is in moderate category. Therefore, the lowest level of writing anxiety is the avoidance behavior, while the highest level of writing anxiety is somatic anxiety.